Smart films fabricated from natural pigments for measurement of total volatile basic nitrogen (TVB-N) content of meat for freshness evaluation: A systematic review. (1st December 2022) - Tahir, Haroon Elrasheid; Hashim, Sulafa B.H.; Komla Mahunu, Gustav; Arslan, Muhammad; Jiyong, Shi; Adam Mariod, Abdalbasit; Zhang, Junjun; El-Seedi, Hesham R.; Zhai, Xiaodong; Musa, Taha H.; Xiaobo, Zou
Graphical abstract: Highlights: This is the first meta -analysis of smart films for tracking meat freshness. The natural pigments had different sensitivities to spoilage indicators. The sensitivity of the natural pigments depends on the spoilage conditions. The overall TVB-N of the spoiled seafood, red meat, and chicken is estimated at 24.96 mg/100 g. The prediction interval was ranged between 23.10 and 26.82 mg/100 g. Abstract: Major databases were searched from January 2012 to August 2021 and 54 eligible studies were included in the meta -analysis to estimate the overall mean of total volatile basic nitrogen (TVB-N) in meat. The mean of TVB-N was 24.96 mg/100 g (95 % CI:23.10–26.82). The pooled estimate of naphthoquinone, curcumin, anthocyanins, alizarin and betalains were 25.98 mg/100 g (95 %CI:19.63–32.33), 30.03 mg/100 g (95 %CI: 24.15–35.91), 24.92 mg/100 g (95 %CI: 22.55–27.30), 23.37 mg/100 g (95 %CI:19.42–27.33) and 19.50 mg/100 g (95 %CI:17.87–21.12), respectively. Meanwhile, subgroups based on meat types showed that smart film was most used in aquatic products at 27.19 mg/100 g (95 %CI:24.97–29.42), followed by red meat at 19.69 mg/100 g (95 %CI:17.44–21.94). Furthermore, 4 °C was the most storage temperature used for testing the performance of smart films at 25.48 mg/100 g (95 %CI:23.05–27.90), followed by storage at 25 °C of 25.65 mg/100 g (95 %CI:22.17–29.13). Substantial heterogeneity was found across the eligible studies (I 2  = 99 %, p  = 0.00). The results of the trim-and-fill method demonstrated publication bias was well controlled.